Implications of the adoption of BISAC for classifying library collections - Martínez-Ávila, Daniel [UNESP]; Kipp, Margaret E.I. (My University, 2014)
We analysed the written statements of libraries that have adopted the bookstore model for coherence or lack of coherence with common public library guidelines. We used a text-based Foucauldian genealogical discourse analysis to investigate the written statements used by libraries that have adopted BISAC and other aspects of the bookstore model. Libraries adopting bookstore models such as BISAC should consider the potential consequences of adopting a commercial model for a public entity. This paper has practical implications for libraries considering adopting any aspect of the bookstore model, but especially the BISAC system, as it examines the potential benefits and drawbacks of the bookstore model popular in some libraries with respect to the purposes and goals of public libraries. BISAC application in libraries seems to be part of a trend of applying commercial practices, values and terminology in libraries, perhaps not with the purpose of replacing libraries with bookstores, but with the aim for both systems to converge into a new kind of commercial entity and context The influence of one kind of system over die other does not seem to be totally reciprocal, since the application of library practices, values and standards in bookstores has not had the same effects and resonance as has occurred in the opposite direction.
Keywords: BISAC; Bookstores; Browsing; Classification; Dewey decimal classification; Public libraries; Users